The Effect of Sock Exercises On Bench Press Achievement Of National League Weightlifters With Special Needs - Jassim, Mouyed; Hamid, Aqeel; Adeeb, Ghassan (Journal of Physical Education, 2018)
The Effect of Sock Exercises On Bench Press Achievement Of National League Weightlifters With Special Needs The research aimed at identifying the effect of shock exercises on achieving bench press from laying position by national league weightlifters with special needs. The researchers used the experimental method. The subjects were (8) national league weightlifters participating in the Asian Championship 2017. The researchers conducted two training sessions per week making a total of 12 training sessions for (6) weeks to conclude that shock exercises affected maximum strength of large muscles of bench press. Finally they recommended the necessity of using these exercises for developing large muscles to achieve bench press from laying position.